Acoustical treatment characterization of a classroom with wood-based composites. (July 2021) - Scoczynski Ribeiro, Rodrigo; Amlani, Amyn M.; de Conto, Juliana; Schwerz, Bruno Germano; Deniz Amarilla, Rosemara Santos; Sant'Ana, Luis Henrique; Avelar, Márcio; Catai, Rodrigo Eduardo; Matoski, Adalberto
Highlights: Nailing wood-based panels on the existing walls is an option for acoustic treatments. WWCB improves intelligibility without absorbing excessive high-frequency energies. A statistical sound absorption coefficient can be used at the mid-frequency range. Abstract: The built environment might be acoustically treated in different ways in terms of complexity and cost. This research proposes an alternative for the acoustical treatment of an existing classroom through the insertion of wooden composites (i.e. panels) which were attached on the walls. This proposition sought to demonstrate an alternative that was easy in the context of implementation and feasible from the perspective of sustainability and cost. Industrialized wood composites from the south part of Brazil were chosen, such as the MDF (Medium Density Fiberboard), the OSB (Oriented Strand Board) and the WWCB (Wood-Wool Cement Board) with different thicknesses. In a acoustically treated classroom, the reverberation time ( T 20 ) and the Speech Transmission Index (STI) were evaluated as objective parameters. Three-dimensional models were built and validated with measurements using an open source software (I-SIMPA) in order to identify which scheme could provide the optimal T 20 . In order to complement the analysis, subjective tests were carried out with a sample of men and women to determine the Word Discrimination Testing (WDT) applied to the classroom environment. WWCB-type panels increased the STI values at different seats over the classroom and the analysis of the Sound Pressure Levels (SPL) distribution along the seats led to the conclusion that there was no excessive absorption of high-frequency energy. Finally, the subjective tests proved that the WWCB type (50.0 mm thick) improved the speech intelligibility.